Using gas dynamic models to improve exhaust system design for large-bore, two-stroke engines. (August 2021) - Bajwa, Abdullah U; Patterson, Mark; Jacobs, Timothy J
It is vital to have accurate predictions of the gas exchange behavior of an engine in order to reliably study engine performance and emissions using engine simulation models. There are a multitude of factors, both upstream and downstream of the engine cylinder, which influence its gas exchange characteristics. Quite often these influences are interconnected in a non-linear manner that results in complicated feedback loops, which can introduce significant errors in the computed thermodynamic state of the post-breathing cylinder mixture. The effects of such bi-directional movement of pressure pulses are particularly pronounced in two-stroke engines. This study investigates the importance of exhaust system design on the scavenging characteristics of a piston-scavenged, cross-flow, two-stroke engine. A validated one-dimensional predictive model is used to study the effects of changing the exhaust port timing, exhaust system length, and exhaust port efficiency on the breathing performance of the engine, along with the consequent effects on the thermal efficiency and NOx emissions. Exhaust pressure waves and mass flows across ports are used to understand and explain the observed changes. The results show that while making design changes, thermodynamic efficiency considerations can act as a barrier to improving the scavenging efficiency of the engine; in addition, a trade-off between the two has to be considered in the design process to meet engine performance targets. The effects of such a trade-off on the NOx production are analyzed and two exhaust system modifications are discussed.